Addressing ethnic disparity in antenatal care: a qualitative evaluation of midwives' experiences with the MAMAACT intervention - Helle Johnsen; Nazila Ghavami Kivi; Cecilie H. Morrison; Mette Juhl; Ulla Christensen; Sarah F. Villadsen (BMC, 2020)
Abstract Background In Denmark, 13% of all children are born by non-Western immigrant women. The public antenatal care has not adapted to this increased diversity of women. Compared to women coming from Western countries, non-Western immigrant women have an increased prevalence of severe maternal morbidity and higher risks of maternal death, stillbirth and infant death. Suboptimal care is a contributing factor to these ethnic disparities, and thus the provision of appropriate antenatal care services is pivotal to reducing these disparities and challenges to public health. Yet, little is known about the targeted interventions which have been developed to reduce these inequities in reproductive health. The MAMAACT intervention, which included a training course for midwives, a leaflet and a mobile application, as well as additional visit time, was developed and tested at a maternity ward to increase responses to pregnancy warning signs among midwives and non-Western immigrant women. Aim: To explore the feasibility and acceptability of the MAMAACT intervention among midwives and identify factors affecting midwives' delivery of the intervention. Methods Eight mini-group interviews with midwives (n = 18) were undertaken. Systematic text condensation was used to analyse data. Results Three main categories were identified, which were 'Challenges of working with non-Western immigrant women', 'Attitudes towards and use of the leaflet and mobile application', and 'Organisational factors affecting the use of the MAMAACT intervention'. Conclusions The MAMAACT intervention was found to be feasible as well as acceptable among midwives. Women turning to relatives for pregnancy-related advice, time constraints during midwifery visits, incomplete clinical records and lack of professional interpreter assistance impacted midwives' delivery of the MAMAACT intervention. Midwives displayed a readiness for the MAMAACT intervention; however, there is a need to further examine how contextual factors may impact the use of the intervention in antenatal care. Trial registration ClinicalTrials.gov, Retrospective Registration (07/2/2020), registration number NCT04261400.